The distribution of mutations and hotspots in transcription regulators of resistance-nodulation-cell division efflux pumps in tigecycline non-susceptible Acinetobacter baumannii in China - Qingye Xu; Xiaoting Hua; Jintao He; Di Zhang; Qiong Chen; Linghong Zhang; Belinda Loh; Sebastian Leptihn; Yurong Wen; Paul G. Higgins; Yunsong Yu; Zhihui Zhou (Elsevier, 2020)
Objective: Acinetobacter baumannii has emerged as a problematic hospital pathogen and tigecycline is among the few remaining antibiotics retaining activity against multidrug-resistant A. baumannii. This study was aimed to elucidate the tigecycline resistance mechanisms in 28 unique clinical A. baumannii strains from nine provinces in China. Methods: Whole genome sequences were obtained via Illumina HiSeq sequencing and regulatory genes of efflux pumps were analyzed. Minimal inhibitory concentrations (MICs) were determined by agar/microbroth dilution according to the guidelines recommended by Clinical and Laboratory Standards Institute (CLSI). Tigecycline susceptibility data was interpreted using breakpoints for Enterobacterales recommended by EUCAST v8.1. Results: The majority of isolates belonged to the international clonal lineage IC2 (n = 27, 96.4%). Four isolates were considered tigecycline-intermediate (MIC = 2 mg/L), twenty-four isolates were tigecycline-resistant. The insertion of ISAba1 in adeS was found in six isolates and was the most prevalent insertion element (IS). In four isolates we observed an insertion of ISAba1 in adeN, and two of them had IS26 insertions. Two mutations in adeN (deletion and premature stop codon) were observed only in the MIC = 4 mg/L isolates. Other mutations in adeRS (amino acid insertion/substitutions and premature stop codons) were only detected in the MIC ≥ 8 group. The novel substitutions E219 K in adeR and A130 T in adeS were observed in five and four isolates respectively, suggesting a mutational hotspot. Conclusions: This study demonstrates that changes in transcription regulators were important mechanisms in tigecycline resistance in A. baumannii. Also, we identified several chromosomal hotspots that can be used for prediction of tigecycline resistance.